Etude des propriétés antioxydantes et antibactériennes de l’extrait Curcuma longa L. - KASSOUS, Nadia; SALEM, Roumaissaa (My University, 2025)
This study is part of a valorization approach for Curcuma longa L., a medicinal plant well-known for its therapeutic and nutritional properties. The main objective of this work was to evaluate the antioxidant and antibacterial activities of plant extracts obtained through two extraction techniques: maceration and discontinuous solid-liquid extraction. These techniques were selected to compare their efficiency in terms of extraction yield and bioactive compound concentration. The results demonstrated superior efficiency of solid-liquid extraction, with a yield of 11.80% compared to 5.10% for maceration. Phytochemical analysis revealed richness in phenols, flavonoids, and tannins, which are responsible for the observed biological activity. Antioxidant activity evaluation was performed using the DPPH method, revealing notable antioxidant potential with an IC₅₀ value of 27.00 μg/ml. Antibacterial activity was investigated using the disc diffusion method, tested against six pathogenic strains: Staphylococcus aureus, Salmonella typhi, Bacillus cereus, Escherichia coli, Bacillus subtilis, and Pseudomonas aeruginosa. Results showed good sensitivity of Gramnegativebacteria as well as GrampositiveStaphylococcus aureus, while B. subtilis and B. cereus proved to be resistant. These observations confirm the potential of Curcuma longa L. as a natural source of antioxidant and antimicrobial agents, which could be valorized in the development of natural preservatives for the agro-food industry or integrated into therapeutic formulations.
Keywords: Curcuma longa L.; maceration; solid-liquid extraction; phenolic compounds; antioxidant activity; antibacterial activity